2-(3-Carboxymethyl-4-nitrophenyl) propionic acid - Huo, L.H.; Ng, S.W.; Zain, Sharifuddin Md; Zhao, H.; Gao, S. (International Union of Crystallography, 2004)
The molecules of 2-(3-Carboxymethyl-4-nitrophenyl)propionic acid were linked by two pairs of hydrogen bonds into a linear chain structure. The nitro group distorts the bond dimensions of the aromatic ring. The energy of the geometry-optimized structure was calculated to be 146.6 kcal mol- more stable than the X-ray structure. The theoretical structure showed no significant distortion of the aromatic ring. It was found that the atom C4 is more positive than the adjacent methylene C atom, whereas atom C6 is more negative than the adjacent methine C atom. Atom C4 and C6 are both more positive than their adjacent neighbors in the crystal structure.